Geographical variation in insecticide resistance in Spodoptera litura to different insecticides - Kitturmath, M S; Sannaveerappanavar, V T (Indian Journal of Plant Protection, 2019)
The bioassay experiments were conducted on Spodopters litura to know the geographical variation in resistance to seven different insecticides belonging to different groups in the Department of Entomology, University of Agricultural Sciences, Bangalore. The field populations of S. litura from three locations of South India viz., Bangalore, Dharwad and Ooty were collected for the bioassay studies. All the three populations differed in their susceptibility to insecticides. The Ooty population exhibited greater levels of resistance to most of the insecticides tested followed by Bangalore population. The Dharwad population was relatively less tolerant to the insecticides. Irrespective of location, the S. litura populations showed moderate to high levels of resistance to monocrotophos (8.48 to 30.96- fold), low to high resistance to cypermethrin (2.92to 21.19- fold) and moderate resistance to endosulfan (3.89 to 11.14- fold) and profenofos (4.79 to 7.22- fold). All three populations exhibited relatively low levels of resistance to methomyl (2.72 to 3.34- fold), indoxacarb (2.11 to 3.10- fold) and novaluron (1.07 to 3.64- fold).